2012
DOI: 10.1038/nature11326
|View full text |Cite
|
Sign up to set email alerts
|

Set2 methylation of histone H3 lysine 36 suppresses histone exchange on transcribed genes

Abstract: Set2-mediated methylation of histone H3 at Lys 36 (H3K36me) is a co-transcriptional event that is necessary for the activation of the Rpd3S histone deacetylase complex, thereby maintaining the coding region of genes in a hypoacetylated state. In the absence of Set2, H3K36 or Rpd3S acetylated histones accumulate on open reading frames (ORFs), leading to transcription initiation from cryptic promoters within ORFs. Although the co-transcriptional deacetylation pathway is well characterized, the factors responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
314
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 295 publications
(342 citation statements)
references
References 36 publications
25
314
1
2
Order By: Relevance
“…36 Studies show that Set2 is associated with the elongating form of RNA Pol II and mediates H3K36me2/me3 to recruit a number of chromatin-modifying complexes (Rpd3S and Isw1b) that maintain a repressive chromatin environment that is resistant to pervasive transcription in the coding regions of genes. [37][38][39][40][41][42] Although a number of studies have shown that the human homolog of Set2, SETD2, is important for alternative splicing 31,33 and that H3K36 is essential for viability in drosophila, 43 the direct role of H3K36me3 and other methylation states (particularly H3K36me2) in both canonical and alternative splicing has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…36 Studies show that Set2 is associated with the elongating form of RNA Pol II and mediates H3K36me2/me3 to recruit a number of chromatin-modifying complexes (Rpd3S and Isw1b) that maintain a repressive chromatin environment that is resistant to pervasive transcription in the coding regions of genes. [37][38][39][40][41][42] Although a number of studies have shown that the human homolog of Set2, SETD2, is important for alternative splicing 31,33 and that H3K36 is essential for viability in drosophila, 43 the direct role of H3K36me3 and other methylation states (particularly H3K36me2) in both canonical and alternative splicing has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In yeast, Set2 mediates all H3K36 methylation states (H3K36me1/me2/ me3) (17) and regulates the recruitment of chromatin-remodeling enzymes (Isw1b) and a histone deacetylase (Rpd3) (18) that functions to keep gene bodies deacetylated, thereby maintaining a more compact chromatin structure (19,20) that is more resistant to inappropriate and bidirectional transcription (18,21). The Set2/SETD2 pathway is also important for DNA repair (22)(23)(24)(25)(26)(27) in both yeast and humans, as well as for proper mRNA splicing (12,28,29).…”
mentioning
confidence: 99%
“…Consistent with this observation, loss of Set2 and Set3 resulted in the recruitment of the IME1-specific transcription factor and NFR formation. Set2-mediated H3K36 methylation has recently been shown to prevent histone exchange over gene bodies [12]. Thus, H3K36 methylation npg over the IME1 promoter may not only result in deacetylation of nucleosomes, but also in decreased histone exchange, leading to the abrogation of the NFR.…”
mentioning
confidence: 99%
“…One of the key features distinguishing these mechanisms from the two papers from the Buratowski and Amon labs is that they act in trans. These papers in Cell highlight the fact that the process of transcribing ncRNAs itself can regulate gene expression from overlapping targets by utilizing the Set2-and Set3-mediated chromatin repression mechanisms [2,3,12,15]. Interestingly, despite the fact that a majority of ncRNAs have relative short half-lives, this mechanism would not be limited by stability issues since the ncRNA itself is not involved in the process of repression.…”
mentioning
confidence: 99%